Treatment of In-Patient Pulmonary Tuberculosis - Rasmin Rasjid (Paediatrica Indonesiana, 1975)
The progress of a tuberculous lesion was discussed. A treatment regimen of pulmonary tuberculosis in the wards mas layed out, especially for the "Persahabatan" Hospital, Jakarta. Rifampicin seems to be a potent drug. However, for developing countries like Indonesia it is still very expensive. Possibly a combinations of INH + RMP + EB will be most effective at present. Only a daily treatment is carried out in â€Persahabatanâ€ Hospital.